Degradable environment-friendly packaging material and preparation process thereof
Compound antibacterial additives are prepared by modifying nanomontmorillonite and hydrothermal reaction, and combined with barrier and toughening modifiers, the problem of insufficient antibacterial performance and durability of existing packaging materials is solved, achieving efficient antibacterial effect and overall improvement of the material.
Patent Information
- Application Number
- CN202510317334.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Existing packaging materials have shortcomings in antibacterial properties and durability, especially in drug packaging, which may cause drug failure or cause health problems.
Compound antibacterial additives are prepared by modifying nanomontmorillonite and hydrothermal reaction, and melt blended with polylactic acid, and added barrier additives and toughening modifiers to prepare degradable and environmentally friendly packaging materials with strong antibacterial properties and durability.
The broad-spectrum antibacterial properties of packaging materials are achieved, the antibacterial validity period is extended, and the overall toughness and barrier properties of the material are improved.
Smart Images

Figure CN119842198A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, and in particular to a degradable and environment-friendly packaging material and a preparation process thereof. Background Art
[0002] Packaging materials are widely used in various fields, from food, medicine to daily necessities, and play a key role in the protection, storage and transportation of products. Traditional packaging materials are mainly petroleum-based plastics, such as polyethylene, polypropylene, polystyrene, etc. Although these materials have the characteristics of low cost, good processing performance, and excellent mechanical properties, they are difficult to degrade in the natural environment. A large amount of discarded plastic packaging garbage accumulates, causing pollution.
[0003] With the continuous improvement of people's environmental awareness and the emphasis on sustainable development, degradable materials have come into being. Degradable materials can be decomposed into small molecules in a short period of time under the action of natural environments such as soil, water, and microorganisms, and return to the natural cycle. Common degradable materials include polylactic acid, polyhydroxyalkanoates, starch-based materials, etc. Polylactic acid uses renewable plant resources (such as corn, sugarcane, etc.) as raw materials, has good biocompatibility and mechanical properties, and has broad application prospects in the packaging field. However, for product packaging such as medicines that have extremely high requirements for hygiene conditions, antibacterial properties are crucial. In pharmaceutical packaging, microbial contamination may cause the drug to fail or even cause serious health problems.
[0004] Most of the existing packaging materials achieve antibacterial performance improvement by adding antibacterial agents. However, some methods use chemically synthesized antibacterial agents, such as antibacterial agents containing heavy metals. Although they have significant antibacterial effects, they may cause potential harm to human health and the environment. In addition, heavy metal ions are difficult to degrade in the environment and may be enriched through the food chain, causing toxic effects on organisms. Natural antibacterial agents, such as chitosan, although they have good biocompatibility and safety, have poor compatibility with degradable materials, are prone to problems such as uneven dispersion during the preparation process, and have poor antibacterial persistence, which can easily affect the overall performance of the material.
[0005] Therefore, it is necessary to propose a biodegradable and environmentally friendly packaging material with good antibacterial properties and long antibacterial durability and a preparation process thereof to improve the overall performance of the packaging material. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention aims to provide a degradable and environmentally friendly packaging material and a preparation process thereof.
[0007] A preparation process of a degradable and environmentally friendly packaging material comprises the following steps: S1: Preparation of modified nano-montmorillonite Firstly, methacrylate (2-dimethylaminoethyl) ester and acrylic acid are dissolved in ethanol to prepare a mixed alcohol solution, and nano-montmorillonite is dispersed in deionized water to prepare a nano-montmorillonite suspension, and then the two are mixed and benzoyl peroxide is added to react to obtain modified nano-montmorillonite; S2: Preparation of composite antimicrobial additives The modified nano-montmorillonite is dispersed in anhydrous ethanol, and tetrahydrofuran and benzyl chloride are added to react to prepare quaternary ammonium salt montmorillonite, which is then dispersed in deionized water, mixed with zinc nitrate solution, and hexamethylenetetramine solution is added to perform hydrothermal reaction to obtain a composite antibacterial additive; S3: Preparation of barrier additives Dimethyl 2,5-furandicarboxylate, dimethyl succinate, neopentyl glycol and zinc acetate are mixed and reacted, and then antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamate are added and continued to react to obtain a barrier additive; S4: Preparation of biodegradable and environmentally friendly packaging materials First, a toughening modifier is prepared with tannic acid and maleic anhydride as raw materials, and then the polylactic acid particles and the toughening modifier are melt-blended, and then the above-mentioned composite antibacterial additive, the above-mentioned barrier additive, polybutylene adipate-terephthalate and cellulose nanocrystal aqueous suspension are added, and melt-blending is continued. After extrusion granulation, film blowing and heat treatment, a degradable and environmentally friendly packaging material is obtained.
[0008] Furthermore, S1 specifically includes the following steps: S1.1: Add 2-dimethylaminoethyl methacrylate and acrylic acid into anhydrous ethanol at a solid-liquid ratio of (8.6-9) g:1 g:(55-65) mL, stir and mix thoroughly to obtain a mixed alcohol solution; S1.2: Add nano-montmorillonite into deionized water at a solid-liquid ratio of 1 g: (45-55) mL, and ultrasonically disperse for 20-30 min to obtain a nano-montmorillonite suspension; S1.3: Add the mixed alcohol solution to the nano-montmorillonite suspension, then add benzoyl peroxide, continue ultrasonic dispersion for 10-20 minutes, then heat the reaction at 70-80°C for 5-6 hours under the protection of nitrogen, cool, centrifuge and wash with ethanol to obtain modified nano-montmorillonite.
[0009] Furthermore, S2 specifically includes the following steps: S2.1: Add the modified nano-montmorillonite prepared in step S1.3 to anhydrous ethanol at a solid-liquid ratio of 1 g: (90-100) mL, ultrasonically disperse for 10-20 min, then add tetrahydrofuran and benzyl chloride, stir and react for 20-24 h, and obtain quaternary ammonium salt montmorillonite after centrifugal separation, ethanol washing and drying, wherein the mass ratios of tetrahydrofuran and benzyl chloride to the modified nano-montmorillonite are (8-9):1 and (2-3):1, respectively; S2.2: Add the above quaternary ammonium salt montmorillonite into deionized water at a solid-liquid ratio of 1 g: (145-155) mL, and ultrasonically disperse for 10-20 min to obtain a quaternary ammonium salt montmorillonite dispersion; S2.3: Add zinc nitrate hexahydrate into deionized water at a solid-liquid ratio of 1 g: (12-14) mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution; S2.4: Add the above zinc nitrate solution to the above quaternary ammonium salt montmorillonite dispersion, ultrasonically treat for 10-20 minutes, then add hexamethylenetetramine solution while stirring to adjust the pH to 8-10, then transfer to a hydrothermal reactor, heat and react at 120-160°C for 6-8 hours, cool, centrifuge, wash and dry to obtain a composite antibacterial additive, wherein the volume ratio of zinc nitrate solution to quaternary ammonium salt montmorillonite dispersion is 1: (6-8), and the mass fraction of hexamethylenetetramine solution is 2-3%.
[0010] Furthermore, S3 specifically includes the following steps: S3.1: Add dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol into a reaction kettle in a molar ratio of 1: (1.2-1.4): (3.3-3.6), then add zinc acetate, and heat and stir at 170-180°C for 3-5h under the protection of nitrogen to obtain an intermediate; S3.2: Add antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamate to the above intermediate, and adjust the heating temperature to 220-240°C. Then turn on the vacuum pump to reduce the pressure in the reactor to 30-50Pa, keep the reaction warm for 4-6 hours, and then introduce nitrogen to restore the pressure in the reactor to atmospheric pressure to obtain the barrier additive.
[0011] Furthermore, S4 specifically includes the following steps: S4.1: Add tannic acid to N,N-dimethylformamide at a solid-liquid ratio of 1 g: (9-11) mL, heat and stir at 40-60°C until completely dissolved to obtain a tannic acid solution; S4.2: Add maleic anhydride and 4-dimethylaminopyridine to the above tannic acid solution, stir well, heat and stir under reflux at 70-90°C for 4-6 hours, cool, pour into deionized water, filter, wash and vacuum dry to obtain a toughening modifier; S4.3: Add the polylactic acid particles and the above toughening and modifying agent into a high-speed mixer, mix them at 60 - 70 °C for 10 - 20 min, then add them into a twin-screw extruder, add antioxidant 1010, and melt-blend at 170 - 190 °C and 100 - 120 r / min for 1 - 2 h to obtain a precursor melt; S4.4: Add the composite antibacterial additive prepared in step S2.4, the barrier additive prepared in step S3.2, poly(butylene adipate-co-terephthalate), and a cellulose nanocrystal aqueous suspension with a mass fraction of 1 - 3% into the above precursor melt, continue to melt-blend for 2 - 3 h, and then extrude and pelletize to obtain a packaging material masterbatch; S4.5: Transfer the above packaging material masterbatch to a single-screw extruder, blow film, and then heat-treat at 40 - 60 °C for 2 - 3 h to obtain a degradable and environmentally friendly packaging material.
[0012] Further, the volume ratio of the mixed alcohol solution to the nanometer montmorillonite suspension is (2 - 3):1, and the mass ratio of benzoyl peroxide to (2-dimethylaminoethyl) methacrylate is 1:(105 - 110).
[0013] Further, the addition amount of zinc acetate is 0.08 - 0.1% of the total mass of dimethyl 2,5-furandicarboxylate, dimethyl succinate, and neopentyl glycol, and the mass ratios of antimony trioxide and octyl 3,5-di-tert-butyl-4-hydroxyhydrocinnamate to zinc acetate are (3.2 - 3.6):1 and (6 - 8):1 respectively.
[0014] Further, the molar ratio of maleic anhydride to tannic acid is (18 - 26):1, and the addition amount of 4-dimethylaminopyridine is 3 - 5% of the mass of tannic acid.
[0015] Further, by mass parts, the packaging material includes: 40 - 50 parts of polylactic acid particles, 15 - 25 parts of cellulose nanocrystal aqueous suspension, 10 - 15 parts of composite antibacterial additive, 8 - 12 parts of barrier additive, 5 - 10 parts of toughening and modifying agent, 6 - 8 parts of poly(butylene adipate-co-terephthalate), and 2 - 3 parts of antioxidant 1010.
[0016] Further, a degradable and environmentally friendly packaging material is prepared by the preparation process of a degradable and environmentally friendly packaging material described in any one of the above.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention first uses methacrylate (2-dimethylaminoethyl) ester and acrylic acid as raw materials, modifies nano-montmorillonite under the initiation of benzoyl peroxide, and then synthesizes nano-zinc oxide in situ on the surface of the quaternized montmorillonite through a hydrothermal reaction after quaternization to prepare a composite antibacterial additive. When the composite antibacterial additive is added to polylactic acid to prepare a packaging material, since the quaternized modified montmorillonite itself has antibacterial ability, the quaternary ammonium salt group can be adsorbed on the surface of bacteria through electrostatic action to destroy the cell membrane structure of the bacteria, and the nano-zinc oxide can combine with biological molecules such as proteins and enzymes in the bacteria to affect the normal metabolism and growth and reproduction of the bacteria, thereby making the composite antibacterial additive The additive has a broad-spectrum antibacterial property and can effectively inhibit the growth of a variety of bacteria, fungi and other microorganisms, giving the packaging material a strong antibacterial protection ability. In addition, nano-montmorillonite has a unique layered structure. After being modified, it is used as a carrier of nano-zinc oxide, which can not only improve the loading effect of nano-zinc oxide, but also effectively improve the dispersibility of nano-zinc oxide in the packaging material, stably load the nano-zinc oxide on its surface and between layers, and further improve the antibacterial effect of the packaging material. When the composite antibacterial additive is added to the packaging material, the modified layered structure can slow down the release rate of the antibacterial components, making the antibacterial effect more lasting, so as to extend the antibacterial validity period of the packaging material.
[0018] 2. The present invention first uses dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol as raw materials, performs an esterification reaction under the catalysis of zinc acetate to prepare an intermediate, then adds antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamate to perform heating and melting polycondensation to prepare a barrier additive, and after the barrier additive is added to polylactic acid to prepare a packaging material, on the one hand, due to the presence of the rigid furan ring in the molecular chain of the barrier additive, the molecular chain movement of the packaging material is relatively restricted, making the overall structure of the material more compact and orderly, reducing the small particles such as gas and water vapor. On the other hand, barrier additives can act as nucleating agents to induce the crystallization of polylactic acid, and the increase in crystallinity will form more crystalline areas inside the material, hindering the penetration of small molecules such as gas and water vapor, thereby effectively improving the barrier properties of packaging materials. In addition, barrier additives affect the barrier structure formed by the crystallization and molecular chain movement of polylactic acid, which is intertwined with the lamellar barrier structure of the composite antibacterial additive to form a composite barrier network, thereby strengthening the network structure's barrier effect on small molecules, which can achieve the effect of synergistically improving the barrier properties of packaging materials.
[0019] 3. The present invention prepares a toughening modifier using tannic acid and maleic anhydride as raw materials, and then melt-blending the toughening modifier with polylactic acid. After the polylactic acid is modified, the toughening modifier and the polylactic acid interact through hydrogen bonds and the like, so that a good interface bonding can be formed between the two. When the packaging material is subjected to external force, the stress can be effectively transferred between the carboxylated tannic acid and the polylactic acid, thus avoiding stress concentration and debonding at the interface, so that the packaging material can better withstand the external force. Moreover, since the toughening modifier can be evenly dispersed in the polylactic acid matrix, when the packaging material is subjected to external force, the stress can be evenly dispersed throughout the entire packaging material system, thus avoiding excessive concentration of stress in a local area, so that the packaging material can more effectively absorb and dissipate energy, thereby improving the overall toughness of the packaging material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0021] Figure 1 This is a flow chart of the preparation process of the degradable and environmentally friendly packaging material used in an embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following describes in detail a degradable and environmentally friendly packaging material and a preparation process thereof provided by the present invention in conjunction with the accompanying drawings and specific embodiments.
[0023] Example 1 A preparation process of a degradable and environmentally friendly packaging material, such as Figure 1 As shown, the following steps are included: S1: Preparation of modified nano-montmorillonite S1.1: Add 2-dimethylaminoethyl methacrylate and acrylic acid into anhydrous ethanol at a solid-liquid ratio of 8.6 g:1 g:55 mL, stir and mix thoroughly to obtain a mixed alcohol solution; S1.2: Add nano-montmorillonite into deionized water at a solid-liquid ratio of 1 g:45 mL, and ultrasonically disperse for 20 min to obtain a nano-montmorillonite suspension; S1.3: adding the mixed alcohol solution to the nano-montmorillonite suspension, and then adding benzoyl peroxide, continuing ultrasonic dispersion for 10 minutes, and then heating the mixture at 70°C for 5 hours under the protection of nitrogen, cooling, centrifuging and washing with ethanol to obtain modified nano-montmorillonite, wherein the volume ratio of the mixed alcohol solution to the nano-montmorillonite suspension is 2:1, and the mass ratio of benzoyl peroxide to methacrylate (2-dimethylaminoethyl) is 1:105; S2: Preparation of composite antimicrobial additives S2.1: Add the modified nano-montmorillonite prepared in step S1.3 to anhydrous ethanol at a solid-liquid ratio of 1g:90mL, ultrasonically disperse for 10 minutes, then add tetrahydrofuran and benzyl chloride, stir and react for 20 hours, and obtain quaternary ammonium salt montmorillonite after centrifugal separation, ethanol washing and drying, wherein the mass ratios of tetrahydrofuran and benzyl chloride to the modified nano-montmorillonite are 8:1 and 2:1 respectively; S2.2: Add the above quaternary ammonium salt montmorillonite into deionized water at a solid-liquid ratio of 1 g:145 mL, and disperse by ultrasonic for 10 min to obtain a quaternary ammonium salt montmorillonite dispersion; S2.3: Add zinc nitrate hexahydrate into deionized water at a solid-liquid ratio of 1 g:12 mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution; S2.4: adding the zinc nitrate solution to the quaternary ammonium salt montmorillonite dispersion, ultrasonically treating for 10 minutes, adding hexamethylenetetramine solution while stirring to adjust the pH to 8, then transferring to a hydrothermal reactor, heating at 120°C for 6 hours, cooling, centrifuging, washing and drying to obtain a composite antibacterial additive, wherein the volume ratio of the zinc nitrate solution to the quaternary ammonium salt montmorillonite dispersion is 1:6, and the mass fraction of the hexamethylenetetramine solution is 2%; S3: Preparation of barrier additives S3.1: Add dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol into a reaction kettle in a molar ratio of 1:1.2:3.3, then add zinc acetate, and heat and stir the reaction at 170°C for 3 hours under the protection of nitrogen to obtain an intermediate, wherein the amount of zinc acetate added is 0.08% of the total mass of dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol; S3.2: Add antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octyl ester to the above intermediate, adjust the heating temperature to 220°C, then start the vacuum pump, reduce the pressure in the reactor to 30Pa, keep the temperature for 4 hours, and then introduce nitrogen to restore the pressure in the reactor to atmospheric pressure to obtain a barrier additive, wherein the mass ratios of antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octyl ester to zinc acetate are 3.2:1 and 6:1 respectively; S4: Preparation of biodegradable and environmentally friendly packaging materials S4.1: Add tannic acid to N,N-dimethylformamide at a solid-liquid ratio of 1 g:9 mL, heat and stir at 40°C until completely dissolved, to obtain a tannic acid solution; S4.2: Add maleic anhydride and 4-dimethylaminopyridine to the above tannic acid solution, stir well, heat and stir under reflux at 70°C for 4 hours, cool, pour into deionized water, filter, wash and vacuum dry to obtain a toughening modifier, wherein the molar ratio of maleic anhydride to tannic acid is 18:1, and the amount of 4-dimethylaminopyridine added is 3% of the mass of tannic acid; S4.3: 40 parts by weight of polylactic acid particles and 5 parts by weight of the toughening modifier are added to a high-speed mixer, mixed at 60° C. for 10 min, then added to a twin-screw extruder, 2 parts by weight of antioxidant 1010 are added, and melt-blended at 170° C. and 100 r / min for 1 h to obtain a precursor melt; S4.4: Add 10 parts by mass of the composite antibacterial additive prepared in step S2.4, 8 parts by mass of the barrier additive prepared in step S3.2, 6 parts by mass of polybutylene adipate terephthalate and 15 parts by mass of a 1% aqueous suspension of cellulose nanocrystals to the above-mentioned precursor melt, continue melt blending for 2 hours, and then granulate by extrusion to obtain a masterbatch of packaging material; S4.5: The above packaging material masterbatch is transferred to a single screw extruder for film blowing, and then heat treated at 40° C. for 2 h to obtain a degradable and environmentally friendly packaging material.
[0024] Example 2 A preparation process of a degradable and environmentally friendly packaging material, such as Figure 1 As shown, the following steps are included: S1: Preparation of modified nano-montmorillonite S1.1: Add 2-dimethylaminoethyl methacrylate and acrylic acid into anhydrous ethanol at a solid-liquid ratio of 8.8 g:1 g:60 mL, stir and mix thoroughly to obtain a mixed alcohol solution; S1.2: Add nano-montmorillonite into deionized water at a solid-liquid ratio of 1g:50mL, and ultrasonically disperse for 25 minutes to obtain a nano-montmorillonite suspension; S1.3: adding the mixed alcohol solution to the nano-montmorillonite suspension, and then adding benzoyl peroxide, continuing ultrasonic dispersion for 15 minutes, and then heating the reaction at 75°C for 5.5 hours under the protection of nitrogen, cooling, centrifuging and washing with ethanol to obtain modified nano-montmorillonite, wherein the volume ratio of the mixed alcohol solution to the nano-montmorillonite suspension is 2.5:1, and the mass ratio of benzoyl peroxide to methacrylate (2-dimethylaminoethyl) is 1:107.5; S2: Preparation of composite antimicrobial additives S2.1: Add the modified nano-montmorillonite prepared in step S1.3 to anhydrous ethanol at a solid-liquid ratio of 1g:95mL, ultrasonically disperse for 15min, then add tetrahydrofuran and benzyl chloride, stir and react for 22h, and obtain quaternary ammonium salt montmorillonite after centrifugal separation, ethanol washing and drying, wherein the mass ratios of tetrahydrofuran and benzyl chloride to the modified nano-montmorillonite are 8.5:1 and 2.5:1 respectively; S2.2: Add the above quaternary ammonium salt montmorillonite into deionized water at a solid-liquid ratio of 1 g:150 mL, and ultrasonically disperse for 15 min to obtain a quaternary ammonium salt montmorillonite dispersion; S2.3: Add zinc nitrate hexahydrate into deionized water at a solid-liquid ratio of 1 g:13 mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution; S2.4: adding the zinc nitrate solution to the quaternary ammonium salt montmorillonite dispersion, ultrasonically treating for 15 minutes, adding hexamethylenetetramine solution while stirring to adjust the pH to 9, then transferring to a hydrothermal reactor, heating at 140°C for 7 hours, cooling, centrifuging, washing and drying to obtain a composite antibacterial additive, wherein the volume ratio of the zinc nitrate solution to the quaternary ammonium salt montmorillonite dispersion is 1:7, and the mass fraction of the hexamethylenetetramine solution is 2.5%; S3: Preparation of barrier additives S3.1: Add dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol into a reaction kettle at a molar ratio of 1:1.3:3.5, then add zinc acetate, and heat and stir the reaction at 175°C for 4 hours under the protection of nitrogen to obtain an intermediate, wherein the amount of zinc acetate added is 0.09% of the total mass of dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol; S3.2: Add antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octyl ester to the above intermediate, adjust the heating temperature to 230°C, then start the vacuum pump, reduce the pressure in the reactor to 40Pa, keep the temperature for reaction for 5 hours, then introduce nitrogen to restore the pressure in the reactor to atmospheric pressure to obtain a barrier additive, wherein the mass ratios of antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octyl ester to zinc acetate are 3.4:1 and 7:1 respectively; S4: Preparation of biodegradable and environmentally friendly packaging materials S4.1: Add tannic acid to N,N-dimethylformamide at a solid-liquid ratio of 1 g:10 mL, heat and stir at 50°C until completely dissolved, to obtain a tannic acid solution; S4.2: Add maleic anhydride and 4-dimethylaminopyridine to the above tannic acid solution, stir well, heat and stir under reflux at 80°C for 5 hours, cool, pour into deionized water, filter, wash and vacuum dry to obtain a toughening modifier, wherein the molar ratio of maleic anhydride to tannic acid is 22:1, and the amount of 4-dimethylaminopyridine added is 4% of the mass of tannic acid; S4.3: 45 parts by weight of polylactic acid particles and 7.5 parts by weight of the toughening modifier are added to a high-speed mixer, mixed at 65° C. for 15 min, then added to a twin-screw extruder, 2.5 parts by weight of antioxidant 1010 are added, and melt-blended at 180° C. and 110 r / min for 1.5 h to obtain a precursor melt; S4.4: Add 12.5 parts by mass of the composite antibacterial additive prepared in step S2.4, 10 parts by mass of the barrier additive prepared in step S3.2, 7 parts by mass of polybutylene adipate terephthalate and 20 parts by mass of a 2% aqueous suspension of cellulose nanocrystals to the above-mentioned precursor melt, continue melt blending for 2.5 hours, and then granulate by extrusion to obtain a packaging material masterbatch; S4.5: The above packaging material masterbatch is transferred to a single screw extruder for film blowing, and then heat treated at 50° C. for 2.5 h to obtain a degradable and environmentally friendly packaging material.
[0025] Example 3 A preparation process of a degradable and environmentally friendly packaging material, such as Figure 1 As shown, the following steps are included: S1: Preparation of modified nano-montmorillonite S1.1: Add 2-dimethylaminoethyl methacrylate and acrylic acid into anhydrous ethanol at a solid-liquid ratio of 9g:1g:65mL, stir and mix thoroughly to obtain a mixed alcohol solution; S1.2: Add nano-montmorillonite into deionized water at a solid-liquid ratio of 1g:55mL, and ultrasonically disperse for 30 minutes to obtain a nano-montmorillonite suspension; S1.3: adding the mixed alcohol solution to the nano-montmorillonite suspension, and then adding benzoyl peroxide, continuing ultrasonic dispersion for 20 minutes, and then heating the mixture at 80°C for 6 hours under the protection of nitrogen, cooling, centrifuging and washing with ethanol to obtain modified nano-montmorillonite, wherein the volume ratio of the mixed alcohol solution to the nano-montmorillonite suspension is 3:1, and the mass ratio of benzoyl peroxide to methacrylate (2-dimethylaminoethyl) is 1:110; S2: Preparation of composite antimicrobial additives S2.1: Add the modified nano-montmorillonite prepared in step S1.3 to anhydrous ethanol at a solid-liquid ratio of 1 g:100 mL, ultrasonically disperse for 20 min, then add tetrahydrofuran and benzyl chloride, stir and react for 24 h, and obtain quaternary ammonium salt montmorillonite after centrifugal separation, ethanol washing and drying, wherein the mass ratios of tetrahydrofuran and benzyl chloride to the modified nano-montmorillonite are 9:1 and 3:1 respectively; S2.2: Add the above quaternary ammonium salt montmorillonite into deionized water at a solid-liquid ratio of 1 g:155 mL, and ultrasonically disperse for 20 min to obtain a quaternary ammonium salt montmorillonite dispersion; S2.3: Add zinc nitrate hexahydrate into deionized water at a solid-liquid ratio of 1 g:14 mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution; S2.4: adding the zinc nitrate solution to the quaternary ammonium salt montmorillonite dispersion, ultrasonically treating for 20 minutes, adding hexamethylenetetramine solution while stirring to adjust the pH to 10, then transferring to a hydrothermal reactor, heating at 160°C for 8 hours, cooling, centrifuging, washing and drying to obtain a composite antibacterial additive, wherein the volume ratio of the zinc nitrate solution to the quaternary ammonium salt montmorillonite dispersion is 1:8, and the mass fraction of the hexamethylenetetramine solution is 3%; S3: Preparation of barrier additives S3.1: Add dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol into a reaction kettle at a molar ratio of 1:1.4:3.6, then add zinc acetate, and heat and stir the reaction at 180°C for 5 hours under the protection of nitrogen to obtain an intermediate, wherein the amount of zinc acetate added is 0.1% of the total mass of dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol; S3.2: Add antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octyl ester to the above intermediate, adjust the heating temperature to 240°C, then start the vacuum pump, reduce the pressure in the reactor to 50Pa, keep the temperature for reaction for 6 hours, and then introduce nitrogen to restore the pressure in the reactor to atmospheric pressure to obtain a barrier additive, wherein the mass ratios of antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octyl ester to zinc acetate are 3.6:1 and 8:1 respectively; S4: Preparation of biodegradable and environmentally friendly packaging materials S4.1: Add tannic acid to N,N-dimethylformamide at a solid-liquid ratio of 1 g:11 mL, heat and stir at 60°C until completely dissolved, to obtain a tannic acid solution; S4.2: Add maleic anhydride and 4-dimethylaminopyridine to the above tannic acid solution, stir well, heat and stir under reflux at 90°C for 6 hours, cool, pour into deionized water, filter, wash and vacuum dry to obtain a toughening modifier, wherein the molar ratio of maleic anhydride to tannic acid is 26:1, and the amount of 4-dimethylaminopyridine added is 5% of the mass of tannic acid; S4.3: 50 parts by weight of polylactic acid particles and 10 parts by weight of the toughening modifier are added to a high-speed mixer, mixed at 70° C. for 20 min, then added to a twin-screw extruder, 3 parts by weight of antioxidant 1010 are added, and melt-blended at 190° C. and 120 r / min for 2 h to obtain a precursor melt; S4.4: Add 15 parts by mass of the composite antibacterial additive prepared in step S2.4, 12 parts by mass of the barrier additive prepared in step S3.2, 8 parts by mass of polybutylene adipate terephthalate and 25 parts by mass of a 3% aqueous suspension of cellulose nanocrystals to the above-mentioned precursor melt, continue melt blending for 3 hours, and then granulate by extrusion to obtain a masterbatch of packaging material; S4.5: The above packaging material masterbatch is transferred to a single screw extruder for film blowing, and then heat treated at 60° C. for 3 h to obtain a degradable and environmentally friendly packaging material.
[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the composite antibacterial additive in step S4.4 is removed.
[0027] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that steps S1.1-S2.1 are removed, and the quaternary ammonium salt montmorillonite in step S2.2 is replaced by an equal amount of nano-montmorillonite.
[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the barrier additive in step S4.4 is removed.
[0029] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the barrier additive in step S4.4 is replaced by an equal amount of a composite antibacterial additive.
[0030] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the composite antimicrobial agent in step S4.4 is replaced by an equal amount of barrier additive.
[0031] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the toughening modifier in step S4.3 is removed.
[0032] Test Case Test 1: Use 10 7 CFU / mL of Escherichia coli suspension and Staphylococcus aureus suspension were used as test bacteria, and the initial antibacterial rates of the packaging materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to standard QB / T2591-2003. The results are shown in Table 1.
[0033] Table 1: Initial antibacterial rate test results of packaging materials
[0034] As can be seen from Table 1, in Comparative Example 1, after no composite antibacterial additive is added, the resistance of the prepared packaging material to Escherichia coli and Staphylococcus aureus is much lower than that of Example 1, indicating that by first using methacrylate (2-dimethylaminoethyl) ester and acrylic acid as raw materials, the nano-montmorillonite is modified under the initiation of benzoyl peroxide, and then quaternized, and then nano-zinc oxide is in situ synthesized on the surface of the quaternized montmorillonite by hydrothermal reaction to prepare a composite antibacterial additive. When the composite antibacterial additive is added to polylactic acid to prepare a packaging material, it can effectively inhibit a variety of bacteria. , fungi and other microorganisms, giving the packaging material a strong antibacterial protection ability. In addition, in Comparative Example 2, after the nano-montmorillonite is not modified, the resistance of the prepared packaging material to Escherichia coli and Staphylococcus aureus is also lower than that in Example 1. It can be seen that after the nano-montmorillonite is modified, it is used as a carrier of nano-zinc oxide, which can not only improve the loading effect of nano-zinc oxide, but also effectively improve the dispersibility of nano-zinc oxide in the packaging material, stably load the nano-zinc oxide on its surface and between layers, and further improve the antibacterial performance of the packaging material.
[0035] Test 2: The packaging materials prepared in Examples 1-3 and Comparative Example 2 were added to deionized water, placed in a constant temperature water bath oscillator at 37°C and shaken at 150 rpm for 30 days, and then the antibacterial rate of the packaging materials after immersion for 30 days was tested according to the method in Test 1. The results are shown in Table 2.
[0036] Table 2: Antibacterial rate test results of packaging materials after immersion for 30 days
[0037] As can be seen from Table 2, in Comparative Example 2, after the nano-montmorillonite is not modified, the antibacterial rate of the prepared packaging material after immersion for 30 days is significantly lower than that of Example 1, indicating that when the composite antibacterial additive is added to the packaging material, the modified layered structure can slow down the release rate of the antibacterial component, making the antibacterial effect more durable, thereby extending the antibacterial validity period of the packaging material; Test 3: The water vapor transmission rate of the packaging materials prepared in Examples 1-3 and Comparative Examples 3-5 was tested using a moisture permeameter, and the oxygen transmission rate of the packaging materials prepared in Examples 1-3 and Comparative Examples 3-5 was tested using an oxygen permeameter. The results are shown in Table 3.
[0038] Table 3: Water vapor transmission rate and oxygen transmission rate test results
[0039] As can be seen from Table 3, after no barrier additive is added in Comparative Example 3, the water vapor transmission rate and oxygen transmission rate of the prepared packaging material are much higher than those in Example 1. It can be seen that by first using dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol as raw materials, carrying out esterification reaction under the catalysis of zinc acetate to prepare an intermediate, and then adding antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamate to carry out heating and melt polycondensation to prepare a barrier additive, and adding the barrier additive to polylactic acid to prepare a packaging material, the barrier performance of the packaging material can be effectively improved; In addition, in Comparative Examples 4 and 5, after the barrier additives were replaced with an equal amount of composite antibacterial additives or the composite antibacterial agent was replaced with an equal amount of barrier additives, the water vapor permeability and oxygen permeability of the prepared packaging materials were also higher than those in Example 1. This shows that the barrier additives and the composite antibacterial additives can synergistically improve the barrier properties of the packaging materials.
[0040] Test 4: The tensile strength of the packaging materials obtained in Examples 1-3 and Comparative Example 6 was tested according to the national standard GB / T1040.3-2006. The results are shown in Table 4.
[0041] Table 4: Tensile strength test results of packaging materials
[0042] As can be seen from Table 4, in Comparative Example 6, after the polylactic acid is modified without using a toughening modifier, the tensile strength of the obtained packaging material is lower than that of Example 1. This shows that by preparing a toughening modifier using tannic acid and maleic anhydride as raw materials and then melt-blending the toughening modifier with polylactic acid to modify the polylactic acid, the overall toughness of the packaging material can be effectively improved.
[0043] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a degradable and environmentally friendly packaging material, characterized in that: The steps include: S1: Preparation of modified nano-montmorillonite Firstly, methacrylate (2-dimethylaminoethyl) ester and acrylic acid are dissolved in ethanol to prepare a mixed alcohol solution, and nano-montmorillonite is dispersed in deionized water to prepare a nano-montmorillonite suspension, and then the two are mixed and benzoyl peroxide is added to react to obtain modified nano-montmorillonite; S2: Preparation of composite antimicrobial additives The modified nano-montmorillonite is dispersed in anhydrous ethanol, and tetrahydrofuran and benzyl chloride are added to react to prepare quaternary ammonium salt montmorillonite, which is then dispersed in deionized water, mixed with zinc nitrate solution, and hexamethylenetetramine solution is added to perform hydrothermal reaction to obtain a composite antibacterial additive; S3: Preparation of barrier additives Dimethyl 2,5-furandicarboxylate, dimethyl succinate, neopentyl glycol and zinc acetate are mixed and reacted, and then antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamate are added and continued to react to obtain a barrier additive; S4: Preparation of biodegradable and environmentally friendly packaging materials First, a toughening modifier is prepared with tannic acid and maleic anhydride as raw materials, and then the polylactic acid particles and the toughening modifier are melt-blended, and then the above-mentioned composite antibacterial additive, the above-mentioned barrier additive, polybutylene adipate-terephthalate and cellulose nanocrystal aqueous suspension are added, and melt-blending is continued. After extrusion granulation, film blowing and heat treatment, a degradable and environmentally friendly packaging material is obtained.
2. The process for preparing a degradable and environmentally friendly packaging material according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Add 2-dimethylaminoethyl methacrylate and acrylic acid into anhydrous ethanol at a solid-liquid ratio of (8.6-9) g:1 g:(55-65) mL, stir and mix thoroughly to obtain a mixed alcohol solution; S1.2: Add nano-montmorillonite into deionized water at a solid-liquid ratio of 1 g: (45-55) mL, and ultrasonically disperse for 20-30 min to obtain a nano-montmorillonite suspension; S1.3: Add the mixed alcohol solution to the nano-montmorillonite suspension, then add benzoyl peroxide, continue ultrasonic dispersion for 10-20 minutes, then heat the reaction at 70-80°C for 5-6 hours under the protection of nitrogen, cool, centrifuge and wash with ethanol to obtain modified nano-montmorillonite.
3. The process for preparing a degradable and environmentally friendly packaging material according to claim 2, characterized in that: S2 specifically includes the following steps: S2.1: Add the modified nano-montmorillonite prepared in step S1.3 to anhydrous ethanol at a solid-liquid ratio of 1 g: (90-100) mL, ultrasonically disperse for 10-20 min, then add tetrahydrofuran and benzyl chloride, stir and react for 20-24 h, and obtain quaternary ammonium salt montmorillonite after centrifugal separation, ethanol washing and drying, wherein the mass ratios of tetrahydrofuran and benzyl chloride to the modified nano-montmorillonite are (8-9):1 and (2-3):1, respectively; S2.2: Add the above quaternary ammonium salt montmorillonite into deionized water at a solid-liquid ratio of 1 g: (145-155) mL, and ultrasonically disperse for 10-20 min to obtain a quaternary ammonium salt montmorillonite dispersion; S2.3: Add zinc nitrate hexahydrate into deionized water at a solid-liquid ratio of 1 g: (12-14) mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution; S2.4: Add the above zinc nitrate solution to the above quaternary ammonium salt montmorillonite dispersion, ultrasonically treat for 10-20 minutes, then add hexamethylenetetramine solution while stirring to adjust the pH to 8-10, then transfer to a hydrothermal reactor, heat and react at 120-160°C for 6-8 hours, cool, centrifuge, wash and dry to obtain a composite antibacterial additive, wherein the volume ratio of zinc nitrate solution to quaternary ammonium salt montmorillonite dispersion is 1: (6-8), and the mass fraction of hexamethylenetetramine solution is 2-3%.
4. The process for preparing a degradable and environmentally friendly packaging material according to claim 3, characterized in that: S3 specifically includes the following steps: S3.1: Add dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol into a reaction kettle in a molar ratio of 1: (1.2-1.4): (3.3-3.6), then add zinc acetate, and heat and stir at 170-180°C for 3-5h under the protection of nitrogen to obtain an intermediate; S3.2: Add antimony trioxide and 3,5-di-tert-butyl-4-hydroxyhydrocinnamate to the above intermediate, and adjust the heating temperature to 220-240°C. Then turn on the vacuum pump to reduce the pressure in the reactor to 30-50Pa, keep the reaction warm for 4-6 hours, and then introduce nitrogen to restore the pressure in the reactor to atmospheric pressure to obtain the barrier additive.
5. The process for preparing a degradable and environmentally friendly packaging material according to claim 4, characterized in that: S4 specifically includes the following steps: S4.1: Add tannic acid to N,N-dimethylformamide at a solid-liquid ratio of 1 g: (9-11) mL, heat and stir at 40-60°C until completely dissolved to obtain a tannic acid solution; S4.2: Add maleic anhydride and 4-dimethylaminopyridine to the above tannic acid solution, stir well, heat and stir under reflux at 70-90°C for 4-6 hours, cool, pour into deionized water, filter, wash and vacuum dry to obtain a toughening modifier; S4.3: Add the polylactic acid particles and the toughening modifier to a high-speed mixer, mix at 60-70°C for 10-20 minutes, add to a twin-screw extruder, add antioxidant 1010, and melt-blend at 170-190°C and 100-120 r / min for 1-2 hours to obtain a precursor melt; S4.4: Add the composite antibacterial additive prepared in step S2.4, the barrier additive prepared in step S3.2, polybutylene adipate-terephthalate and a 1-3% by mass aqueous suspension of cellulose nanocrystals to the above-mentioned precursor melt, continue melt blending for 2-3 hours, and then granulate by extrusion to obtain a packaging material masterbatch; S4.5: The above packaging material masterbatch is transferred to a single screw extruder for film blowing, and then heat treated at 40-60°C for 2-3h to obtain a degradable and environmentally friendly packaging material.
6. The process for preparing a degradable and environmentally friendly packaging material according to claim 2, characterized in that: The volume ratio of the mixed alcohol solution to the nano-montmorillonite suspension is (2-3):1, and the mass ratio of benzoyl peroxide to (2-dimethylaminoethyl) methacrylate is 1:(105-110).
7. The process for preparing a degradable and environmentally friendly packaging material according to claim 4, characterized in that: The amount of zinc acetate added is 0.08-0.1% of the total mass of dimethyl 2,5-furandicarboxylate, dimethyl succinate and neopentyl glycol, and the mass ratios of antimony trioxide and octyl 3,5-di-tert-butyl-4-hydroxyhydrocinnamate to zinc acetate are (3.2-3.6):1 and (6-8):1, respectively.
8. The process for preparing a degradable and environmentally friendly packaging material according to claim 5, characterized in that: The molar ratio of maleic anhydride to tannic acid is (18-26):1, and the amount of 4-dimethylaminopyridine added is 3-5% of the mass of tannic acid.
9. The process for preparing a degradable and environmentally friendly packaging material according to claim 5, characterized in that: The packaging material includes, by weight: 40-50 parts of polylactic acid particles, 15-25 parts of cellulose nanocrystal aqueous suspension, 10-15 parts of composite antibacterial additives, 8-12 parts of barrier additives, 5-10 parts of toughening modifiers, 6-8 parts of polybutylene adipate terephthalate and 2-3 parts of antioxidant 1010.
10. A degradable and environmentally friendly packaging material, characterized in that: The biodegradable environmentally friendly packaging material is prepared by the preparation process of the biodegradable environmentally friendly packaging material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Highly antibacterial PLA (polylactic acid) / PBAT (polybutylene adipate terephthalate) material as well as preparation method and application thereof
CN108752884A
Multi-layer flexible packaging material and preparation process thereof
CN118288585A
High-toughness packaging film and preparation method thereof
CN119039751A
Preparation method of modified montmorillonite antibacterial agent and application of modified montmorillonite antibacterial agent in modified atmosphere preservative film
CN119307010A
Bacteriostatic high-barrier nanocellulose-based composite film for fresh keeping of fruits and vegetables and preparation method of bacteriostatic high-barrier nanocellulose-based composite film
CN119552397A
Cited By
PET packaging material
CN120464147A
A PET packaging material
CN120464147B
Preparation method of antibacterial modified polylactic acid for packaging material
CN121182165A
Process for preparing an antibacterial modified polylactic acid for packaging material
CN121182165B
Antibacterial antifouling polymer composite material as well as preparation method and application thereof
CN122213673A